Significance of FSHR and LHCGR gene polymorphisms on clinical outcomes in gonadotropin-releasing hormone antagonist protocol with freeze-all strategy: A case-control study - Jayesh Amin; Naga Sandhya Alle; Ami Patel; Bansi Prajapathi; Paresh Makwana; Jaya Prakash; Kota Murali Krishna (International Journal of Reproductive BioMedicine)
Abstract Background: Follicle-stimulating hormone receptor (FSHR) and luteinizing hormone/choriogonadotropin receptor (LHCGR) are integral to ovarian function, facilitating follicle development and maturation through their respective hormonal interactions. The influence of receptor polymorphisms on the outcomes of freeze-all cycles remains unclear. Objective: This study investigates the impact of FSHR N680S and LHCGR N312S polymorphisms on clinical outcomes in freeze-all cycles. Materials and Methods: Women undergoing controlled ovarian stimulation for assisted reproductive technology participated in this study. They were administered a gonadotropin-releasing hormone antagonist protocol, with recombinant follicle-stimulating hormone (rFSH) dosages adjusted according to age, body mass index, antral follicle count, and individual hormonal responses. Additionally, human menopausal gonadotropin dosages were tailored based on the LHCGR N312S genetic variant. Results: Analysis revealed no significant differences in age, body mass index, antral follicle count, or marital status across the genotypes of FSHR N680S and LHCGR N312S. However, notable differences were observed in the rFSH dosage required daily and in total among the FSHR polymorphism genotypes. Genotypes of the LHCGR polymorphism correlated with fewer stimulation days. A significant interaction was observed between the 2 polymorphisms concerning total rFSH dosage. Conclusion: The presence of serine in the FSHR polymorphism was associated with higher rFSH dosage requirements. Both FSHR N680S and LHCGR N312S polymorphisms significantly influenced clinical pregnancy and live birth outcomes in freeze-all cycles, underscoring the potential of a pharmacogenomic approach to optimize hormone supplementation in controlled ovarian stimulation protocols during assisted reproductive technology treatments.